The experiences of Australian lesbian couples becoming parents: deciding, searching and birthing - Chapman, Rosemary; Wardrop, Joan; Zappia, Tess; Watkins, Rochelle; Shields, Linda (Wiley-Blackwell Publishing Ltd., 2012)
Aim and objectives: To explore Australian lesbian mothers’ experiences of becoming parents. Background: Lesbians are becoming parents and, since legislative changes in Australia, their numbers are increasing. Prior to legislative changes, fertility and health services for women in Australia exclusively served the needs of the heterosexual community. Although lesbian experience of seeking health services has been studied in other contexts, little has been done to understand their experience of deciding, conceiving and birthing. Design: Qualitative descriptive study. Method: Seven interviews conducted with lesbian mothers in Australia. Results: The following themes were identified: ‘making the decision’; ‘the search’; ‘perseverance’; and ‘problems of isolation’. Conclusions: Although legislation now affords lesbians access to reproductive technologies throughout most of Australia, their involvement with health professionals can result in homophobic interactions. One way to address the needs of lesbian families is to provide an environment where the disclosure of sexual identity is encouraged. Further larger scale research should identify changes to service provision required to address the inequalities between heterosexual and lesbian women and ensure health services are provided that are free from discrimination. Relevance to clinical practice: Most health services have policies and procedures in place to prevent discrimination on all grounds, including sexual orientation. It is imperative that administrators and clinicians take steps to ensure that these guidelines are applied.